Perceptions of telecare training needs in home healthcare services: a focus group study - Guise, Veslemøy (BMC Health Serv Res, 2017)
BACKGROUND: The implementation and use of telecare requires significant changes to healthcare service organisation and delivery, including new ways of working for staff. Competency development and training for healthcare professionals is therefore required to enable necessary adaptation of clinical practice and ensure competent provision of telecare services. It is however unclear what skills healthcare staff need when providing care at a distance and there is little empirical evidence on effective training strategies for telecare practice. Training should however emphasise the experiences and preferences of prospective trainees to ensure its relevance to their educational needs. The aim of this study was to explore healthcare professionals’ perceptions of training related to the general use of telecare, and to identify specific training needs associated with the use of virtual visits in the home healthcare services. METHODS: Six focus group interviews were held with a total of 26 participants working in the home healthcare services in Norway, including registered nurses, enrolled nurses, physiotherapists, occupational therapists, social workers, health workers, and healthcare assistants. The data material was analysed by way of systematic text condensation. RESULTS: The analysis resulted in five categories relevant to telecare training for healthcare professionals: Purposeful training creates confidence and changes attitudes; Training needs depend on ability to cope with telecare; The timing of training; Training must facilitate practical insight into the patients’ perspective; and Training content must focus on the telecare process. Findings are discussed in light of implications for the form and content of a training program for healthcare professionals on how to undertake virtual home healthcare visits. CONCLUSION: Appropriate preparation and training for telecare use is important for healthcare professionals and must be taken seriously by healthcare organisations. To facilitate the knowledge, skills and attitudes required for new ways of working and enable quality and safety in telecare practice, staff should be provided with training as part of telecare implementation processes. Telecare training should be hands-on and encourage an overall patient-centred approach to care to ensure good patient-professional relationships at a distance.